2007
DOI: 10.1007/s10681-007-9376-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic improvement of grain yield and associated traits in the southern China winter wheat region: 1949 to 2000

Abstract: To understand the genetic gains of grain yield in the Southern China Winter Wheat Region (SCWWR), two yield potential trials, i.e., YPT 1 including 11 leading cultivars from the Middle and Low Yangtze Valley (Zone III) and YPT 2 including 15 leading cultivars from the Southwestern China Region (Zone IV) from 1949 to 2000, were conduced during the 2001-2003 cropping seasons. A completely randomized block design of three replicates was employed with controlled field environments. Molecular markers were used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
50
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 20 publications
(22 reference statements)
11
50
2
Order By: Relevance
“…However, any further reductions in plant height will limit aboveground biomass. We found no significant increase in aboveground biomass at maturity with year of release, which is consistent with other studies [17,27,43]. In future, higher yields will require breeder commitment to increasing aboveground biomass [28], which can be supported by increasing the resistance of different internodes to lodging without reducing plant height.…”
Section: Plant Height and Internode Lengthsupporting
confidence: 91%
See 2 more Smart Citations
“…However, any further reductions in plant height will limit aboveground biomass. We found no significant increase in aboveground biomass at maturity with year of release, which is consistent with other studies [17,27,43]. In future, higher yields will require breeder commitment to increasing aboveground biomass [28], which can be supported by increasing the resistance of different internodes to lodging without reducing plant height.…”
Section: Plant Height and Internode Lengthsupporting
confidence: 91%
“…Yields of winter wheat in the western Yellow and Huai Valley increased by 3.95g m −2 yr −1 from 1948 to 2012, more than that in Nanjing (14 kg ha −1 yr −1 ), similar to that in Chengdu (41 kg ha −1 yr −1 ) in southern China [27], and less than the 60 kg ha −1 yr −1 in the northern wheat region of China [20], 62 kg ha −1 yr −1 in Shandong Province [22], 57.5 kg ha −1 yr −1 in the southern Yellow and Huai Valley [28], and 51.30 and 70 kg ha −1 yr −1 reported in Henan Province [18,29,30]. Some researchers believe that increases in yield are directly related to TGW or grain number per spike [18,31,32]; this study found that TGW contributed more to yield increases than GN (Table 3).…”
Section: Evolution Of Yield and Yield-related Traitsmentioning
confidence: 81%
See 1 more Smart Citation
“…Various researchers have reported genetic progress in yield potential and agronomic and physiological characteristics of wheat cultivars in diff erent regions (Waddington et al, 1986;Hucl and Baker, 1987;Slafer and Andrade, 1989;Calderini et al, 1995;Sayre et al, 1997;Ortiz-Monasterio et al, 1997;Brancourt-Hulmel et al, 2003;Shearman et al, 2005;Zhou et al 2007aZhou et al , 2007bGraybosch and Peterson, 2010). Mean annual genetic gains for spring wheat ranged from 0.5% during 1982 to 1985 in Canada (Hucl and Baker, 1987) to 1.5% during 1950 to 1982 in Mexico (Waddington et al, 1986).…”
mentioning
confidence: 99%
“…It is common to present the gain per year as a percentage of the mean yield for the crop under study. In this way, most rates of progress correspond to less than 1% (e.g., Zhou et al, 2007a). Peng et al (2000) evaluated the genetic gain for irrigated rice, based on 12 rice cultivars developed at the International Rice Research Institute (IRRI), in the period of 1966 to 1995, resulting in a genetic gain of 75 to 81 kg ha −1 yr −1 , corresponding to 1% per year.…”
mentioning
confidence: 99%